Consumptive Behavior and Saving Ring Workers; Case Study In Cihideunghilir Kuningan Village - Abdul Aziz (Al-Musthofa: Journal of Sharia Economics, 2019)
Income is the response from what we do such as salary, rent interest, commission, expanse, and profit. The ring craftsman gets income from making a ring, andthat income will use to consuming thing or merits that they need. The high income can increase consumption ability and make the consumption higher. The high income can increase saving ability. Problem formulation in this research is first is the income influential to the consumption pattern of ring craftsman at Cihideunghilir Village Cidahu Subdistrict Kuningan Regency. Two is the income influential to saving ability of ring craftsman at Cihideunghilir Village Cidahu Kuningan West Java.